"Investigação dos Processos de Subjetivação": Por um Riso de Rua Político e Performativo - Campaneli, Keila Sírio (2020)
The present research is a practical-theoretical research where I approach the processes of subjectivation, from the concepctions of Felix Guattari (1986) under the perspective of an approximation between the art of clown and the art of performance, whose base is also found in the relation of the problematic of poverty in the street population. Therefore, I try to combine the concepts related to the investigation of laughter proposed by the author Georges Minois (2003) and the scenic production of the clown described by Mário F. Bolognesi (2003) with a study with the propositions of Félix Guattari (1981) and Fernando G. Rey (2003) about the themes linked to the production of subjectivities, and supported by the studies and propositions on the performance art of Renato Ferracini (2003) and Renato Cohen (2011), which describe the limits between the performance art in contemporary theatrical performance. In order to discuss the clown-performers relationship, the research is developed and articulated, considering the street population as a motto for research, based on the voices of people in the street situation in which the field study was carried out, being this, the Reference Center for homeless people - Centro POP and the Casa de Acolhimento Santa Gemma, both located in the city of Uberlândia-MG.